The delicate balance between Entamoeba histolytica, mucus and microbiota - Leon-Coria, Aralia (Gut Microbes, 2019)
Entamoeba histolytica (Eh) is a protozoan parasite of humans that colonizes the outer colonic mucus layer. Under conditions not fully understood, Eh breaches innate host defenses and invades the intestinal mucosa-causing amebic colitis and liver abscess. In asymptomatic infection, Eh interacts with and feeds on resident microbiota that forms biofilms on the outer colonic mucus layer. Despite the close association between Eh and commensal microbiota, we still lack basic knowledge on whether microbiota and/or their metabolites influence Eh virulence traits critical in disease pathogenesis. In the pathogenesis of intestinal amebiasis, Eh overcomes the protective mucus layer using a combination of mucinase/glycosidase and potent mucus secretagogue activity. In this addendum, we discuss the interconnected role of a healthy mucus barrier and the role commensal microbiota play in shaping innate host defense against Eh-induced pro-inflammatory and secretory responses critical in disease pathogenesis.